Chitosan films and chitosan/pectin polyelectrolyte complexes encapsulating silver sulfadiazine for wound healing - (:unkn) unknown (ISTANBUL UNIV, FAC PHARMACY, 2020)
Background and Aims: The use of natural polymers as wound dressings is attracting more interest due to their favoured properties such as biodegradability and biocompatibility. With this background, chitosan films and chitosan/pectin polyelectrolyte complex films encapsulating silver sulfadiazine were fabricated as novel wound dressings. Methods: Films were fabricated, and the surface topography and the surface roughness of the films were characterised by atomic force microscopy. Swelling and hydrolytic degradation behaviours of the films were monitored, and surface chemistry analysis was carried out. Following drug release studies, release kinetics were studied to evaluate the films for drug delivery. Results: Results suggest that the characteristic crystalline structure of chitosan films disappears after complexation with pectin. Polyelectrolyte complex films were found to be more durable than chitosan films due to their improved resistance to hydrolytic degradation. No incompatibilities amongst formulation components were detected. In vitro drug release studies indicated a rapid release of the drug from chitosan films compared to polyelectrolyte complex films. Conclusion: The overall results suggest that chitosan/pectin polyelectrolyte complex films have improved properties in terms of durability compared to chitosan films. Both films could be a promising candidate for wound healing applications considering the specific needs of different types of wounds.
Keywords: Chitosan; silver sulfadiazine; polyelectrolyte; RELEASE; DRESSINGS; DELIVERY; CHITIN; BURNS